Objective Landscapes: The Mediated Evidence of Repeat Photography - McManus, Karla (Intermédialités / Intermediality, 2011)
Repeat photography, which involves re-photographing a location from the same vantage point, has become a common method to document the changes occurring in the landscape. Artists, ecologists, geologists and anthropologists alike have employed this practice. What unites these disciplines across great ideological and cultural distances is their understanding of photography as a truthful witness to the passage of time. This position places great value on the mechanical observation of the camera and the objectivity of the photographer. The article focuses on one example of this practice: the Rocky Mountain Repeat Photography Project, an academic research project, illustrates the complexities inherent in claiming photography, or the photographer, as a neutral observer free of ideological and cultural concerns.